Peran Musyawarah Guru Mata Pelajaran dalam Meningkatkan Profesionalisme Guru Pendidikan Agama Islam SMA - Janafi, Ozi; Satria, Rengga (Prodi Pendidikan Keagamaan Islam, 2023)
The problem in this study is the low professionalism of PAI teachers as evidenced by the low UKG scores and the existence of PAI teachers who always use the same method in learning coupled with the less role of subject teacher deliberations (MGMP) in improving competence. This study aims to determine the role of subject teacher deliberations (MGMP) in improving the professionalism of Islamic religious education teachers in SMA in South Solok Regency and the obstacles it faces. This type of research is qualitative. Sources of data in the study were taken through observation, interviews, and documentation. Data analysis techniques are data reduction, data presentation, and drawing conclusions. Test the validity of the data using triangulation. The results of this study indicate that MGMP has an important role in increasing teacher professionalism, especially in improving pedagogic competence, personality competence, professional competence, and social competence by conducting ongoing training, inviting speakers from outside the region, training in the use of IT-based media, making and adapting models. learning, making learning tools, and providing solutions to problems faced by teachers. The obstacles faced by the MGMP are 1) Long distances and lack of motivation to participate in MGMP activities. 2) There is no assistance from schools and the government for MGMP in finding the honorarium for invited speakers and other costs. 3) Discipline of members who are lacking in starting the event. 4) The teaching schedule is attached to the MGMP activities.